What can COVID‐19 pandemic reveal about public purpose of a University? A case study. Issue 199 (3rd November 2022) - Mohebali, Milad
Abstract: This case study examines institutional communication of purpose to stakeholders through Facebook during the COVID‐19 pandemic. The findings show that the institution attempted to reduce the negative impacts of the pandemic on campus life and student experiences while using the pandemic as an opportunity to re‐iterate the importance of its scientific knowledge production, training of professionals, and service to communities. In doing so, it established relationships with multiple publics at a time of crisis, but has run the risk of further losing public trust in science and university as the COVID‐19 pandemic has persisted.